Follicle-like tertiary lymphoid structures: A potential biomarker for prognosis and immunotherapy response in patients with laryngeal squamous cell carcinoma - Liang, Haifeng; Zhang, Zhigang; Guan, Zhong; Zheng, Shibie; Lou, Jintao; Liu, Wei; Cai, Qian; Si, Yu (Frontiers in Immunology, 2023)
Background The maturity and spatial distribution of tertiary lymphoid structures (TLSs) vary dynamically within and between cancers, leading to a controversial role in cancer. We aimed to develop a simple morphology-based approach to identify the maturity of TLSs in laryngeal squamous cell carcinoma and examine their clinically relevant functional role. Methods TLSs were identified based on morphological features via hematoxylin and eosin (H&E) staining, and the accuracy was verified by multi-immunohistochemical analysis. The density, maturity, spatial distribution and prognostic value of TLSs were separately analyzed in two human laryngeal cancer cohorts. The TLS profile was linked to RNA-seq data from the TCGA database to perform bioinformatics analysis. Results TLSs can be classified as early TLSs (E-TLSs), primary follicle-like TLSs (PFL-TLSs) and secondary follicle-like TLSs (SFL-TLSs). The three types of TLSs showed higher infiltration in the extratumoral region. XCL2 is a vital chemokine in the maturation and infiltration of TLSs. FL-TLS was an independent positive prognostic indicator in laryngeal cancer. The FL-TLS group had more abundant immune cell infiltration and a better response to immunotherapies than the non-FL-TLS group. Functional analysis showed that the non-FL-TLS group was enriched in tumor invasion, metastasis and immunosuppression pathways. Conclusion The maturity of TLSs can be accurately classified by H&E staining. FL-TLS is a potential mediator of antitumor immunity in human laryngeal cancer.